The Role of Women in the Work of Salvation Through the Figures of Mary and Elisabeth According to Luke Chapters 1–2 - Arif Wicaksono; Adelina Ayu Wangi Kurniawan; Iswahyudi Iswahyudi (RERUM: Journal of Biblical Practice, 2021)
In this day and age, the discussion about women is never-ending and is still a polemic for some people. The position of women who sit lower than men is still a matter in society. There are even some parts of society that restrict women from carrying out their roles only in the domestic sphere, namely only carrying out their roles as a wife and mother in the household. Not only in the community but also in the church environment where women are still weak and do not have a position in the church so that women do not have the same rights and obligations as men. Therefore, women do not have the space to appear in public and are very basic and even not allowed at all. The author conducted this research intending to take the text about women in the Gospel of Luke chapters 1 - 2 through the figures of Mary and Elizabeth. The author uses the narrative critical method by focusing his attention on the characters, plot, setting, and point of view. By using this method, it is hoped that we will get an understanding – both theory and implication in practical living that women also have a very important role in the work of mankind's salvation. God can use women to take part in the declaration of his plan in the world, the effort to save mankind. Therefore, women do not need to think of themselves as inferior to men.